A brief outline of forestry - Holroyd, Hartley Bowen (My University, 1903)
Introduction: The science of forestry treats of the care, purpose and utilization, of the forested areas of the earth, together with the best means of regenerating the forested areas. AT one time the greater part of the earth was covered with a sylva differing in variety according to the climate and soil of the several countries. Through the careIess and injudicious utilization of these areas, they became greatly reduced and the soil in many cases greatly deteriorated. With this factor came the necessity of action toward a more economical use of the resources given us by nature. So the science of forestry, in its different branches, gradually grew into prominence. The various questions arising under forestry have been economically and scientifically dealt with for many years in India, Germany, Switzerland and England but it is only of later years that the science of forestry has shown a marked development in the United States. In order to obtain the most economical results, the control of forests should, with a few exceptions, be under the supervision of the government. In state forestry the interests of the private individual are brought into harmony with the interests of the community as a whole and both derive a mutual benefit. This is exemplified in case of protection forests which are maintained on account of their influence upon the welfare of the community of a large expanse of country. For example, forests which are maintained to prevent denudation, land-slips, to prevent erosion and the silting up of fertile lands at the foot of hills, as a protection where shifting sand occurs, and the preservation and regulation of the water supply in springs and rivers. State forests are considered as a suitable source of public revenue as the income is regular, sustained and safe, and it is a source of income, the payment of which, is not a burden upon the people. They also act in the capacity of a reserve fund which is available for the security of bonds or other pledges. Forestry is the more profitable when conducted on large areas, requiring therefore a larger outlay of capital, which only in exceptional cases is at the disposal of the individual. The state, we suppose, lasts forever and the cost of utilizing the forests will be reimbursed even after the lapse of considerable time even if the rate of interest be small on the capital invested.
Citation: Holroyd, Hartley Bowen. A brief outline of forestry. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Forestry; Foreest Management; Theses